KETIMPANGAN PENDAPATAN PERKAPITA DI PULAU SUMATERA TAHUN 2003-2013 - Utari Antika; Mardiana '; Taryono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to analyze the disparities income per capita in Sumatera year 2003-2013. Where will the results of this study can be seen for what disparities. In addition to knowing imbalance occurs between regions or inter-region. The analysis used in this study is a qualitative analysis based on the theory as well as the opinions of experts who are already applicable to the public. The formula used in this research that Williamson index and Theil entropy index. From the calculation results obtained during the observation period (2003-2013) to the island of Sumatra as follows: the average disparities income per capita in Sumatera by using IW during the observation period (2003 -2013) are 0,00764. Disparities average income per capita by Entropi Theil index for within and between Sumatra during the observation period (2003-2013) are 0,35634 dan 0,08211. By using the index calculation Williamson the highest disparities in 2004. While using the Theil entropy index calculation within province is greater than between region.Keywords: income per capita, population, income per capita disparities, Williamson index, Theil entropy index